The Child who must not cry - Uwaleke, James (Literamed Publications Nigeria Ltd, 2003)
The Child Who Must Not Cry is a story based on human frailties, steeped in the deep African culture,custom,traditions and superstition. It posits that stubbornness,wickedness,greed and cultic practices never pay.
Keywords: Fantasy; Fiction; Juvenile Literature